The Islamic Formalism Movement in Malay Land: Experiences of the Muslim Community in Kerinci, Jambi - Marjan Fadil; Martunus Rahim; Indra Ikhsan (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
This article aims to analyze the development of Islamic religious movements in the Malay traditional land of Kerinci Jambi, particularly related to the tendency of religious formalism in Islamic communities. The pattern of education, local customs and traditions, as well as religious ideology contributed to the emergence of a Muslim community that only paid attention to the formal side of religion or known as formalist Islam. This study uses an anthropological approach through interviews, observations, and documentation of Muslim communities in Kerinci Jambi. This paper finds that formalist Islam tends to be difficult to develop in Malay society exclusively from indigenous groups, and more easily accepted for inclusive societies from immigrant groups or mixing with outsiders and academics. This exclusive Malay community seeks to maintain the Islamic ideology that has been institutionalized in the structure of society that does not contradict between custom and religion since the first, namely Islam with the nuances of Sufism, based on the Shafi'i Madhhab in fiqh, and al-Ghazali Madhhab in theology. Meanwhile, inclusive societies tend to be open to accepting various Islamic identities and most of them do not hold strong traditional values. Artikel ini bertujuan untuk menganalisis perkembangan gerakan keagamaan Islam di tanah adat Melayu Kerinci Jambi, khususnya terkait kecenderungan formalisme keberagamaan komunitas-komunitas Islam. Pola pendidikan, adat dan tradisi lokal, serta ideologi keagamaan memberi kontribusi bagi kemunculan komunitas Muslim yang hanya memperhatikan sisi formal agama saja atau dikenal dengan Islam formalis. Studi ini menggunakan pendekatan antropologis melalui wawancara, observasi dan dokumentasi terhadap komunitas-komunitas Muslim yang terdapat di Kerinci Jambi. Tulisan ini menemukan bahwa Islam formalis cenderung sulit berkembang dalam masyarakat Melayu eksklusif dari golongan masyarakat pribumi, dan lebih mudah diterima bagi masyarakat inklusif dari golongan pendatang atau percampuran dengan masyarakat luar dan para akademisi. Masyarakat Melayu eksklusif ini berupaya mempertahankan ideologi Islam yang telah melembaga dalam struktur masyarakat yang tidak mempertentangkan antara adat dan agama semenjak dahulu yakni Islam dengan nuansa tasawuf, bermazhab Syafi’i dalam fikih, dan bermazhab al-Ghazali dalam teologi. Sedangkan masyarakat inklusif cenderung terbuka menerima beragam identitas Islam dan mereka sebagian besar tidak memegang nilai adat secara kuat.